Improving the marketing activities of medical institutions (for example, clinic number 6 in the city of Uralsk, West Kazakhstan region) - B. B. Sukhanberdina; B. Widmann; G. K. Kurmanova; Z. Zh. Shaihiev; B. A. Urazova (Экономика: стратегия и практика, 2020)
The modern market of medical services of the Republic of Kazakhstan is demonopolized. There are state and private medical institutions in the market that compete with each other.Given the limited financing of the health system and the transfer of outpatient facilities to economic management, the combination of improving the quality and accessibility of medical services for the population and the profitability of the institutions themselves is an important and rather difficult task. In the present study, this problem is proposed to be solved by applying marketing.A modern understanding of the purpose of marketing is not to maximize profits, but to meet the basic needs of the population, ensuring the availability of socially significant goods and services. This emphasizes the social orientation of modern marketing and the achievement of a balance of three marketing goals: satisfying the needs of consumers, maximizing the profits of producers and taking into account the interests of society.In the course of the analysis of the theoretical and methodological aspects of marketing medical services, as well as evaluating the marketing activities of Polyclinic No. 6 of Uralsk, it was revealed that, by improving marketing activities, outpatient organizations are able to compete with private medical institutions, in addition maintain and improve the quality medical services provided.The article gives a theoretical and practical justification for the marketing of medical services in a modern economy and develops a marketing model for clinic number 6 in the city of Uralsk, West Kazakhstan region.